Linkages Among Asset Markets in the United States : Tests in a Bivariate GARCH Framework - Deb, Parha; Darbar, Salim (Washington, D.C. : International Monetary Fund, 1999)
This paper develops a bivariate GARCH model that allows for time-varying conditional correlations and simultaneous testing of two Granger-causal linkages: the impact of return volatility in a market on intermarket correlation and the impact of return volatility in one market on the volatility of another. Using daily data from stock, bond, currency, and commodity markets in the United States, the paper finds evidence of each form of linkage. Furthermore, the conditional correlations change over time and exhibit considerable persistence. The estimated time-varying conditional correlations provide insight into the nature of the stock market crash of 1987.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet